Differences in lower extremity biomechanics, shank muscle activation and medial gastrocnemius–tendon unit behavior between novice and experienced non-rearfoot strike runners - Suo, Bokai; Lu, Zeyu; Wang, Jichao; Wu, Kaicheng; Deng, Liqin; Li, Lu; Zhong, Yunjian; Fu, Weijie (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeThis study aimed to investigate the differences in lower extremity kinematics and kinetics, shank muscle activation, and medial gastrocnemius–tendon unit behavior between habitual rearfoot strike (RFS) runners and habitual non-rearfoot strike (NRFS) runners when adopting an NRFS pattern.MethodsTwelve male habitual RFS runners (novice NRFS runners, NN) and twelve male habitual NRFS runners (experienced NRFS runners, EN) were recruited. All participants were required to run at 9 km/h on the split-belt 3D instrumented treadmill using an NRFS pattern. 3D lower extremity kinematics and kinetics, surface electromyography (sEMG) signals of medial and lateral gastrocnemius (MG and LG), soleus (SOL), and tibialis anterior (TA), as well as dynamic ultrasound imaging of MG tendon unit behavior during running were collected synchronously. Intergroup comparisons were performed using independent samples t-tests and Mann–Whitney U tests, with Significance levels (α) adjusted via Bonferroni correction.ResultsCompared to EN, NN exhibited significantly greater fascicle shortening lengths (NN: 1.54 ± 0.66 cm; EN: 0.94 ± 0.23 cm; p = 0.013) and muscle–tendon unit (MTU) shortening lengths (NN: 3.45 ± 0.51 cm; EN: 1.96 ± 0.23 cm; p < 0.001) of MG. No intergroup differences were observed in lower extremity kinematics, kinetics, or shank muscle activation.ConclusionWhile novice and experienced NRFS runners exhibited similar kinematic, kinetic and muscle activation characteristics, the increased fascicle and muscle–tendon unit shortening lengths of medial gastrocnemius in novice NRFS runners potentially reflect reduced muscle contraction efficiency.